Healthcare Costs and Treatment Patterns of Triplet Therapies in Relapsed/Refractory Multiple Myeloma: Real World Evidence from Italy - Perrone V; Leogrande M; Giacomini E; Cappuccilli M; Degli Esposti L (ClinicoEconomics and Outcomes Research, 2025)
Valentina Perrone, Melania Leogrande, Elisa Giacomini, Maria Cappuccilli, Luca Degli Esposti On behalf of the LHU study groupCliCon S.R.L. Società Benefit, Health Economics and Outcomes Research, Bologna, ItalyCorrespondence: Valentina Perrone, CliCon S.R.L. Società Benefit - Health, Economics and Outcomes Research, Via Murri 9, Bologna, 40137, Italy, Tel +3954438393, Fax +39544212699, Email valentina.perrone@clicon.itPurpose: This analysis sought to characterize patients with relapsed or refractory multiple myeloma (RRMM) on triplet therapy with immunomodulatory agents/proteasome inhibitors/monoclonal antibodies combined with dexamethasone, describing their demographic and clinical features, therapeutic pathways and the related healthcare costs for the Italian National Health Service (NHS).Patients and Methods: A retrospective observational analysis was conducted on administrative databases of Italian healthcare entities, covering about 3.6 million health-assisted residents. From 2017 to 2020, patients receiving at least one triplet combination reimbursed by the Italian NHS for the treatment of RRMM were included. RRMM treatment pathways were evaluated in terms of duration of therapy and treatment lines. Healthcare costs per patient were assessed on monthly basis during the therapy period by computing expenditures for drugs, hospitalizations and outpatient specialist services.Results: A total of 209 RRMM patients on triplet combinations were identified, with a mean age of 67.4 years, 56% males and mild-to-moderate comorbidity profile, with heart disease and renal disease as the most common coexisting conditions (respectively, 13.4% and 7.7% of patients). KRd (carfilzomib/lenalidomide/dexamethasone) was the triplet administrated to the largest proportion of patients (44%), then DaraRd (daratumumab/lenalidomide/dexamethasone) triplet (24%). Treatment duration was on average 7 months for overall patients, 7.7 months for 118 patients with triplet as second line at inclusion, and 6 months for 91 patients with triplet as third or further line at inclusion. The monthly overall costs were € 9,517, with drug expenses accounting for 93% of total expenditures. Progressing to later treatment lines, cost analysis showed comparable trends, being drugs as the most impactive item.Conclusion: This analysis on RRMM patients under triplet medication in real-life Italian clinical practice confirmed the complex multifaceted profile of this frail population, highlighting a challenging clinical management for the oncologists and a major economic burden for the NHS.Keywords: triplet combination therapy, immunomodulatory agents, proteasome inhibitors, monoclonal antibodies, duration of therapy, treatment lines, cost analysis